Food policy analyses and prioritisation of food systems to achieve safer food for South Africa - Tshilidzi Isaac Dama; Olwethu Loki; Wegayehu Fitawek; Sikwela M. Mpuzu (Applied Food Research)
Food safety has become an important international public health and economic issue since the first and only publication of global estimates on the burden of food borne diseases by the World Food Organisation in 2015. The consumption of unsafe food has had a detrimental effect on public health and economic development due to productivity loss, chronic diseases, and death because of the consumption of unsafe food. The challenges that constrain the provision of safe food in South Africa's food systems and potential solutions were identified through a systematic literature review and meta-analysis. Identified potential solutions were then ranked through stakeholder interviews. Twelve actions from various thematic focuses were prioritised as no-regret solutions using Best-Worst scaling. The prioritised no-regret actions include research and technology actions such as the multi-sectoral collaboration of researchers to develop strategies to deal with the complexity of food systems and identify priorities for interventions, adopting technological innovations throughout the value chain to improve food safety, strengthen laboratory diagnostic services, and conducting more research studies on the use of easy-to-understand food safety labels to improve awareness. The no-regret options prioritised are feasible and provide the basis for policy interventions to improve food safety and achieve developmental goals. This study recommended harmonising the legislative framework to improve stakeholder collaboration and accelerate the much-needed transformation of the food systems.